2015
DOI: 10.1007/s11104-015-2617-z
|View full text |Cite
|
Sign up to set email alerts
|

Epichloë endophytes affect the nutrient and fiber content of Lolium perenne regardless of plant genotype

Abstract: Background and Aims: Epichloë endophytes inhabit aerial grass tissues but they can modify belowground processes that might affect host nutrient balance. We aimed to determine the effects of endophyte status (E+=endophyte-infected; E−=non-infected) and three Epichloë morphotypes (M1,M2,M3) on growth and nutrient content of a heterogeneous set of naturally infected asymptomatic plants of Lolium perenne. In addition, plant parameters were compared between asymptomatic E+ and plants with choke disease. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…This suggests that the Epichloid may not decrease the benefit of the endophyte-grass symbiosis by reducing soil fertility. Soto-Barajas et al (2016) using several Epichloë endophytes and Lolium perenne showed also that endophyte-infected plants had significantly lower P, Ca, S, B, neutral detergent fiber and lignin contents, and higher Mn and digestibility than non-inoculated plants, independently of the plant origin. Biomass production was not affected by endophytes but by the plant origin.…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 90%
See 1 more Smart Citation
“…This suggests that the Epichloid may not decrease the benefit of the endophyte-grass symbiosis by reducing soil fertility. Soto-Barajas et al (2016) using several Epichloë endophytes and Lolium perenne showed also that endophyte-infected plants had significantly lower P, Ca, S, B, neutral detergent fiber and lignin contents, and higher Mn and digestibility than non-inoculated plants, independently of the plant origin. Biomass production was not affected by endophytes but by the plant origin.…”
Section: Foliar Endophytes and Below-ground Processesmentioning
confidence: 90%
“…Soussi et al (2016) provided a comprehensive overview of the microbial diversity in arid lands and deserts versus specific microbial assemblages associated with the endosphere of plants. Discussion about the drivers shaping the endophytic diversity, on how plant-associated microbiomes are selected, and on their biotechnological potential was well provided.…”
Section: Endophytes Microbiome and Extreme Conditionsmentioning
confidence: 99%
“…populations infected with E. occultans exhibit peramines (Sugawara et al 2006), N-acetylnorlolines and N-formyllolines (Moore et al 2015) in variable concentrations according to plant organs, phenological stage and geographical origin. As documented for domestic herbivores consuming other grass species (Oliveira et al 2004;Zabalgogeazcoa et al 2006;Soto-Barajas et al 2016), patterns of plant nutritional values and digestibility associated with endophyte presence in L. multiflorum might influence animal preference. Nevertheless, in addition to fungal alkaloids, several studies suggest that epichloid endophytes may exert further ecophysiological and metabolomic effects (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…We analysed those traits usually affecting preference by domestic herbivores (Bailey et al 1996;Jung et al 1997) that, in turn, can be also modified by the endophyte (Miranda et al 2011;Soto-Barajas et al 2016). We analysed those traits usually affecting preference by domestic herbivores (Bailey et al 1996;Jung et al 1997) that, in turn, can be also modified by the endophyte (Miranda et al 2011;Soto-Barajas et al 2016).…”
Section: Plant and Animal Measurementsmentioning
confidence: 99%
See 1 more Smart Citation